Conflict Mediation Based on Local Wisdom: Study on Customary Dispute Resolution in Pelompek Village, Gunung Tujuh, Kerinci (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This study aims to analyze the role of a custom mediator (Depati Niniak Mamak) in resolving customary disputes at Pelompek Village, Kerinci Regency. This research is qualitative and the data were obtained through observation, in-depth interviews, and documentation. The data were analyzed through the following stages: data reduction, data presentation and drawing conclusions or verification. The validity of the data was tested by using the triangulation technique. The results show: 1) several disputes that have occurred in the indigenous people of Pelompek village in recent years are disputes over the unilateral management of TKD by the village since 2014, the dispute over the management of the Telun Berasap waterfall between the village community and the tourism office in 2019, the dispute between the village head and the Panwaslu in 2019, and the theft of cinnamon by residents in early August 2021, 2) supporting factors for resolving customary disputes in the Pelompek community are: a) the capacity of the depati ninik mamak in resolving disputes, and b) the motivation of the disputing parties themselves to resolve disputes. 3) inhibiting factors for dispute resolution: a) emotional feelings of both parties to the dispute, and b) lack understanding of customary law.